St. Miguel Febres Cordero research awardees - Somera, Rene (Animo Repository, 1999)
Dr. Rene Somera of the Behavioral Sciences Department and Dr. Severino Gervacio of the Mathematics Department were named this year's St. Miguel Febres Cordero Research Awardees during the Annual Faculty Recognition.